Single crystal substrates effect on the critical behavior in La2/3Ca1/3MnO3 thin films (2013)
ABSTRACT: In this work we study the substrate influence in magnetic properties and the critical behavior of La2/3Ca1/3MnO3 thin films grown on single-crystal substrate of LaAlO3, SrTiO3 and NdGaO3, using a DC magnetron sputtering system. All films were growth under the same conditions and with thicknesses close to 130nm. We made measures of magnetization as a function of temperature between 150 and 300 K, around critical temperature (Tc) with different external applied magnetic fields (100 Oe – 30 kOe). X rays measures were made to verify the existence of La2/3Ca1/3MnO3 (LCMO) phase, where we observed two peaks corresponding to the samples with Miller index (020) and (040) that verify the presence of LCMO phase in these thin films. Furthermore, critical exponent (β) was obtained fitting the magnetic measures with a proposed model. β values for each substrate are around 0.25, 0.27 y 0.36, that show an important influence of substrate.